Adam Citings before the Intrusion of Satan: Recontextualizing Paul's Theology of Sin and Death - Kelly, Henry Ansgar (Biblical theology bulletin, 2014)
The article surveys early references to the story of Adam and Eve, which are surprisingly few in number, beginning only around 200 bce, with the Book of Tobit. The common notion that Adam was punished by death for his sin is verified neither in Genesis 2–3 itself (and the surrounding chapters) nor in any pre-Pauline texts. Paul's focus on Adam's sin was out of the ordinary, and his conclusion that he was punished by some kind of death does not resemble interpretations in any other contemporary source, including Philo. The equally common idea that the Devil was assumed to participate in causing Adam's sin does not occur in early texts (for instance, Wisdom or the books of the New Testament), being first found in Justin Martyr. Therefore, assessments of biblical theology that depend on these concepts should be emended.